On the taxonomy of genus Termioptycha Meyrick, 1889 (Pyralidae, Epipaschiinae) with description of two new species and two new species records from India - Ranjan, Rahul; Singh, Navneet; Kirti, Jagbir Singh (Zootaxa, 2022)
In the present research paper we describe two new species of Epipaschiinae, Termioptycha gnathospina Ranjan, N. Singh & Kirti, sp. nov. and Termioptycha almae Ranjan, N. Singh & Kirti, sp. nov. and report of two species, Termioptycha cornutitrifurca Rong & Li, 2017 and Termioptycha bilineata (Wileman, 1911) for the first time from India. An updated checklist of all the Termioptycha species is provided.